27x^3 = 1
Subtract 1 from both sides :
27x^3 - 1 = 0
Change to difference of two cubes form :
(3x)^3 - 1^3 = 0
Factorise : e.g. a^3 - b^3 = (a - b)(a^2 + ab + b^2)
(3x - 1)(9x^2 + 3x + 1) = 0
Therefore, 3x - 1 = 0, implying that x = 1/3
or, 9x^2 + 3x + 1 = 0 implying that x = -1/6 ± i*sqrt(3)/6,
after using the quadratic formula.
The 3 solutions are thus: 1/3, -1/6 + i*sqrt(3)/6, -1/6 - i*sqrt(3)/6.
2007-01-27 14:15:21
·
answer #1
·
answered by falzoon 7
·
0⤊
0⤋
x= 1/3
2007-01-27 13:15:30
·
answer #2
·
answered by mazo 1
·
0⤊
0⤋
Solve: 27x^3 =1
First: isolate "x^3" on one side > divide both terms by "27"...
(27x^3)/27 = 1/27
Sec: cancel "like" terms...
x^3 = 1/27
Third: find the cube root of "3" on both sides...
V`(x^3) = V`(1/27)
x = 1/(V`27)
x = 1/(V`3*3*3)
x = 1/3
2007-01-27 15:50:42
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
First get x^3 on one side. This can be done by dividing both sides by 27, leaving you with x^3 = 1/27.
To get rid of the power-to-3, just take the cube root of both sides:
(x^3)^(1/3) = (1/27)^(1/3)
x = (1/27)^(1/3)
Distribute the cube root through both the numerator and denominator:
x = (1^(1/3)) / (27^(1/3))
x = 1 / 3
2007-01-27 13:16:05
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Sure.
27x^3 = 1
x^3 = 1/27
cube root (x^3) = x = cube root(1/27) = 1/3
x = 1/3
Simple, no?
Doug
2007-01-27 13:15:59
·
answer #5
·
answered by doug_donaghue 7
·
0⤊
0⤋
27x^3=1
x^3= 1/27 (divided 27 for both sides)
x= 1/3 (take a cube root)
2007-01-27 13:13:53
·
answer #6
·
answered by 7
·
0⤊
0⤋
The order of operations indicates that exponentiation comes before multiplication.
Divide both sides by 27. This will yield:
x^3 = 1/27
To solve for x, take the cube root of both sides.
2007-01-27 13:14:17
·
answer #7
·
answered by The Iron Star 2
·
0⤊
0⤋
First divide both sides by 27: x^3 = 1/27
Then do the cube root of both sides, since the cube root of x cubed is just x. You can figure the cube root of 1/27.
2007-01-27 13:14:30
·
answer #8
·
answered by hayharbr 7
·
0⤊
0⤋
cubed root of 1 divided by 27
2007-01-27 13:20:14
·
answer #9
·
answered by easy_target06 2
·
0⤊
1⤋
.a million(x+50)+.1x=6 circumstances .a million by potential of whats interior the brackets keep in ideas BEDMAS .1x+5+.1x=6 flow the 5 to the different edge in order to isolate the variable x (once you flow a kind to the different edge of the equals signal it is going to change into adverse) .1x+.1x=a million convey mutually like words .2x=a million divide .2 on both edge to isolate x .2x/.2x=a million/.2 x=5 you are able to plug 5 again into the equation and if each edge are equivalent then its top in case you pick to envision your answer.
2016-10-17 03:45:22
·
answer #10
·
answered by ? 4
·
0⤊
0⤋